2007
DOI: 10.1530/rep-07-0229
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian follicular cells have innate immune capabilities that modulate their endocrine function

Abstract: Oestrogens are pivotal in ovarian follicular growth, development and function, with fundamental roles in steroidogenesis, nurturing the oocyte and ovulation. Infections with bacteria such as Escherichia coli cause infertility in mammals at least in part by perturbing ovarian follicle function, characterised by suppression of oestradiol production. Ovarian follicle granulosa cells produce oestradiol by aromatisation of androstenedione from the theca cells, under the regulation of gonadotrophins such as FSH. Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
311
2
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(337 citation statements)
references
References 54 publications
18
311
2
6
Order By: Relevance
“…In addition to being detected in the uterus and peripheral circulation, LPS has been detected in follicular fluid of cattle with uterine disease; unsurprisingly, concentrations of LPS are directly correlated with bacterial load. Mateus et al, 2003;Herath et al, 2007;. Administration of intravenous LPS disrupts neuroendocrine activity and results in interference with the oestrous cycle.…”
Section: Postpartum Uterine Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to being detected in the uterus and peripheral circulation, LPS has been detected in follicular fluid of cattle with uterine disease; unsurprisingly, concentrations of LPS are directly correlated with bacterial load. Mateus et al, 2003;Herath et al, 2007;. Administration of intravenous LPS disrupts neuroendocrine activity and results in interference with the oestrous cycle.…”
Section: Postpartum Uterine Healthmentioning
confidence: 99%
“…These studies provide evidence for localized effects of LPS in the ovary. Indeed, in vitro LPS has been shown to disrupt granulosa cell oestradiol secretion via reduced expression of aromatase enzyme expression (Herath et al, 2007) and acute exposure to LPS increases follicular atresia and reduces the primordial ovarian follicle pool (Bromfield and Sheldon, 2013).…”
Section: Postpartum Uterine Healthmentioning
confidence: 99%
“…A variety of bioactive molecules (e.g. TNF-α, NO, and PGF2-α, among many others) from the infected mammary gland are released into the bloodstream which have the capacity to disrupt tissues involved in reproduction, such as the ovary (Herath et al 2007), hypothalamus (Schrick et al 2001, Nugent et al 2002, and endometrium (Herath et al 2009). Additionally, follicle growth (Herath et al 2007), and oocyte and embryonic development (Soto et al 2003) are also hampered by endotoxins.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α, NO, and PGF2-α, among many others) from the infected mammary gland are released into the bloodstream which have the capacity to disrupt tissues involved in reproduction, such as the ovary (Herath et al 2007), hypothalamus (Schrick et al 2001, Nugent et al 2002, and endometrium (Herath et al 2009). Additionally, follicle growth (Herath et al 2007), and oocyte and embryonic development (Soto et al 2003) are also hampered by endotoxins. Finally, it should be noted that heat stress (Roth and Wolfenson 2016) and subclinical ketosis (Albaaj et al 2017) seem to have an additive deleterious effect together with CM on fertility of dairy cows.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, we have shown that animals with high numbers of the recognised uterine pathogens including E. coli have retarded ovarian follicle growth, lower peripheral plasma concentrations of oestradiol and an inability to form a competent corpus luteum (CL) ( Table 1; Williams et al, 2007). Lipopolysaccharide (LPS), the main pathogenic moiety of E. coli, is detectable in the uterus, peripheral plasma and ovarian follicular fluid of cows with post partum uterine infection (Peter et al, 1989;Mateus et al, 2003;Herath et al, 2007;Williams et al, 2007). Administration of intravenous LPS disrupts neuroendocrine activity and results in interference with the oestrous cycle.…”
Section: Effects Of E Coli In the Whole Animalmentioning
confidence: 99%